Differential clinical outcomes after 3 versus 5 years in a comparison of preoperative chemotherapy with and without radiotherapy in locally advanced rectal cancer: A national cohort propensity score-matched study - Yuanxin Zhang; Rui Luo; Jingqi Peng; Zichuan He; Delin Tan; Xueping Liu; Hui Wang; Huaiming Wang (Heliyon, 2024)
Background: Preoperative chemotherapy alone might be a good alternative to preoperative chemoradiotherapy for patients with locally advanced rectal cancer, yet long-term real-world data from the same cohort are lacking. Methods: Patients diagnosed with stage II-III rectal adenocarcinoma from 2011 to 2015 were randomly sampled from the SEER-Plus database to evaluate the superiority of preoperative chemoradiotherapy versus preoperative chemotherapy alone. Findings: A total of 1314 eligible patients were enrolled, with a median follow-up of 74.0 months. At 3-year follow-up, neither overall survival (OS) nor cancer-specific survival (CSS) was significantly different between the two treatment groups. At 5-year follow-up, CSS was similar across groups (HR 0.768, 95% CI 0.532–1.108; P = 0.156), but the 5-year OS was significantly better in the preoperative chemoradiotherapy group than in the preoperative chemotherapy group (HR 0.682, 95% CI 0.538–0.866; P = 0.002). Besides, the landmark analysis indicated a direct contrast in the CSS within 3 years (HR 1.101, 95% CI 0.598–2.029; P = 0.756) versus that at 3–5 years (HR 0.597, 95% CI 0.377–0.948; P = 0.027). The landmark analysis also showed directly contrasting OS outcomes within 3 years (HR 0.761, 95% CI 0.533–1.086; P = 0.130) versus those at 3–5 years (HR 0.621, 95% CI 0.451–0.857; P = 0.003). Interpretation: In patients with locally advanced rectal cancer under real-world treatment practices, the addition of preoperative radiotherapy to chemotherapy improves survival outcomes at 3–5 years’ follow-up but not at 3-year follow-up.